Gemstones for Highly Sensitive People - Leupen, Alex (Homœopathic Links, 2018)
Alex Leupen has worked in the Homeopathic Doctors Centre in Utrecht, the Netherlands, since 1990. Eight colleagues work in this centre, including Jan Scholten. Alex is an experienced teacher (the Netherlands, Belgium and Germany) on the underlying systems in the plant families, animal kingdom, sarcodes, nosodes, fungi and the periodic table of the elements pertaining to homeopathic practice. In this column, he shares clinical tips.
Keywords: Gemstones; Highly sensitive persons; Heat; Pressure; Amethyst